6x=6=9x=3

Simple and best practice solution for 6x=6=9x=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x=6=9x=3 equation:



6x=6=9x=3
We move all terms to the left:
6x-(6)=0
We move all terms containing x to the left, all other terms to the right
6x=6
x=6/6
x=1

See similar equations:

| 7x-4(4)=12 | | s+217=757 | | 16=b÷-4 | | v/11=25 | | 5v/13=25/36 | | -21r=756 | | 16=b÷14 | | k-941=-454 | | (x+76)+(3x)=90 | | x+(x+4)+(x+8)=39 | | 7j−7=49 | | 3^(x-3)=243 | | 78-5=3x-31 | | -74=f+-60 | | x-876=987 | | y-14=-72 | | x+1286=1599 | | q-216q=20 | | 21+m=60 | | 4x=⅓ | | 66=u—-35 | | 4l+3+-9=-13 | | 75.3=42.0(1+2d) | | 2.15r+8.50=30 | | -76=f+10 | | 8.50r+2.15=30 | | 47x=2726 | | j/9=-6 | | Y=9x1/10 | | 2/3h-5=11 | | c+-65=3 | | 8=2-6u |

Equations solver categories